Propuesta de un sistema de gestión de la contaminación sonora en la ciudad de Andahuaylas, Apurímac, 2016 - Sichez Muñoz, Julio César (2018)
This work is a contribution to the achievement of sustainable development of the city of Andahuaylas. Its objectives were to identify the level of noise pollution in the city of Andahuaylas, determine the level of anxiety of the population exposed to noise pollution in the city of Andahuaylas, determine the relationship between the level of noise pollution and anxiety of the population exposed to noise pollution in the city of Andahuaylas and propose a Management System for Sound Pollution in the city of Andahuaylas. The research is non-experimental, correlational transectional, and based on the results a Sound Pollution Management System is proposed. The conclusions were that the level of anxiety that predominates is moderate anxiety (66.7%), the noise level that prevails is regular noise (83.3%), there is a significant positive moderate correlation between Anxiety and Noise (r = 0.258) ( p = 0.011), that is, at a higher intensity of noise, anxiety increases moderately in the inhabitants of the city of Andahuaylas. Before the Chi square test, there is a significant relationship between anxiety and noise levels (p = 0.000). When faced with the risk test, exposure to regular noise constitutes a very high risk for moderate anxiety (OR = 6.2), that is, there is a 6.2 times higher risk for residents to experience moderate anxiety if they are exposed to regular noise, than to low noise Keywords: Sound pollution,